Survival, Growth, and Food Resources of Juvenile Sea Cucumbers Holothuria forskali (Echinodermata, Holothuroidea) in Co-Culture with Shellfish in Brittany (France) - Frank David; Grégory Raymond; Julien Grys; Nadia Ameziane; Bastien Sadoul (Aquaculture Nutrition)
We conducted experiments with various growing conditions, both at sea and indoors, to explore the growth potential of Holothuria (Panningothuria) forskali Delle Chiaje, 1823 juveniles. Sea trials involved co-culture with European abalones (EA) or placement underneath European flat oysters (EO) or Pacific oysters (PO), using juveniles of 6–8 g initial weight. In sea-based conditions around summer (Apr–Sep), sea cucumbers grew best in EO at 0.94% d−1, followed by EA (0.88% d−1), both being in deep water (8–12 m), while sea cucumbers in the foreshore of a mega-tidal environment (PO) had the lowest growth (0.24% d−1). The indoor trial (IM) was performed with smaller individuals (≈0.3 g) and yielded a remarkable growth of 2.76% d−1 during summer (May–Sep). All experiments resulted in high survival rates, exceeding 80%. Additionally, we analysed fatty acid, amino acid, and stable isotope compositions of sea cucumbers’ body walls, along with the pigment composition of their stomach contents. These analyses provided evidence that juveniles had distinct diets in each rearing condition, all differing from the diet of adults found in the wild. Our results also demonstrate that sea cucumbers do not compete for food resources in the shellfish production, which is crucial for their integration into multi-trophic aquaculture systems. However, whether sea cucumbers may have benefitted from the organic matter from shellfish faeces and pseudofaeces and/or grew on the biofilm growing on the cage walls remains to be elucidated.